From the Editor on Obesity in Pregnancy - Pacheco Romero, José (2017)
According to the Practice Bulletin number 156, obesity is the most common health care problem in women of reproductive age(1). Implications related to pregnancy are often unrecognized, overlooked, or ignored because of the lack of specific evidence-based treatment options.